Effect of Cat Stretch Exercise and Adho Mukha Padmasana Pose on Dymenoreh Emotional Stability in Students at SMA City of Palembang - Heni Sumastri; Dahliana Dahliana; Indah Puji Seperia (Budapest International Research and Critics University, 2022)
Adho Mukha Padmasana is one of the yoga postures, this movement helps reduce pain during menstruation, strengthens leg muscles, tightens hips and massages thighs and ankles, relaxes mind and stomach. Teenage girls experience several problems during menstruation. Cycle is not smooth, pain, emotional disturbances, changes in attitude (emotionally unstable) and decreased self-confidence. Objective: To determine the effectiveness of the Cat Stretch Exercise and the Adho Mukha Padmasana Pose Technique for the Management of Dysmenorrhea in Young Women during the Covid-19 Pandemic Period in 2021. Research Methods: This research is a quantitative study with a pre-experimental method. The design of this study used One Group Pre-Test-Posttest, using purposive sampling. The results of this study can be seen that from 60 respondents the menstrual pain scale can be reduced after the intervention of the Cat Stretch Exercise and Adho Mukha Padmasana Pose. It is known that the p value <0.01 means that there is at least one variable that has a significant relationship with the intervention carried out, therefore a Wilcoxon multivariate posthoc was performed. To minimize emotional instability due to the influence of the menstrual cycle, habituation exercises are applied.